Pusat Kecantikan Di Pekanbaru Dengan Pendekatan Arsitektur Organik - Laura Arifah Hanum; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Beauty Center is a place where women can perform body care from head to toe. The beauty center has four main facilities Beauty Plaza, where visitors can buy all kinds of beauty care products, Beauty Center is the place to toe treatment, Beauty Gallery isefforts to maintain health, beauty from inside and outside, freshness and relaxation to balance the body, mind and soul (mind, body & spirit) both with a source of minerals, massages, aromatherapy and herbs, as well as Beauty Clinic is beauty services by focusing on service health. This method uses the theme of organic architecture of Frank Lloyd Wringht as a form of architecture of buildings that can be fused and friendly to the natural surroundings so as to provide comfort and relaxation to visitors. As a result of this design to apply the concept Refresh, so that visitors can indulge, relax yourself from everyday activities that create stress and pressure so as to beautify themselves from the outside and the inside. Keywords: Beauty Cnter, Organic Architecture Frank Lloyd Wright, Relaxation, Refresh